Study on the Potential of Inundation area by tsunami in Ciamis Coastal of West Java - Anita Zaitunah; Cecep Kusmana; I Nengah Surati Jaya; Oteng Haridjaja (FORESTA, 2012)
Indonesia has experienced many earthquakes and tsunamis. Tsunamis had caused heavy destruction and deaths. The aim of the study is to find out spatially the potential of inundation area by tsunami. GIS analysis was conducted using Arcview software to obtain an elevation map and the potential of inundation area caused by tsunami. The run up of 7.5 m flooded 4% from whole study area. When the run up was 7,5 m, some areas were flooded reaching 200 m from the coast and there were also some points going further to 1 km. The information on the distance and extent of inundation from by tsunami can become an input on potential areas flooded by water and having destruction.Key words : tsunami, inundation, coastal area, West Java